How do immigrants name their children in France ? - (:unkn) unknown (My University, 2019)
The first names chosen by the majority population and by immigrants' descendants in France are not converging towards typically "French" names but rather towards international names that everyone can identify with. Many children and grandchildren of immigrants from North Africa continue to receive Arab-Muslim first names while some receive new first names (Yanis, Rayane, or Lina) that the majority population perceives as North African.
Keywords: African Research